Design for need : the social contribution of design : an anthology of papers presented to the symposium at the Royal College of Art, London, April, 1976 - Bicknell, Julian; McQuiston, Liz (Published for ICSID by Pergamon Press, 1977)
Design for Need: The Social Contribution of Design compiles papers presented at the Symposium at the Royal College of Art, London in April 1976. This book focuses on the concept of design as a conditioning, reformist, and practical element in society, which examines and demonstrates actual projects carried out in response to social needs. The topics discussed include the industrial design in dependent countries; social forces that determine the shape of technology; role of the designer in disaster relief; reduction of need by design; role of the artist in a hospital environment; and Lucas work.